2005
DOI: 10.1021/bi050931t
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Cytoplasmic Domain of Erythrocyte Membrane Band 3 Determined by Site-Directed Spin Labeling

Abstract: The cytoplasmic domain of the anion exchange protein (cdb3) serves as a critical organizing center for protein-protein interactions that stabilize the erythrocyte membrane. The structure of the central core of cdb3, determined by X-ray crystallography from crystals grown at pH 4.8, revealed a compact dimer for residues 55-356 and unresolved N- and C-termini on each monomer [Zhang et al. (2000) Blood 96, 2925-2933]. Given that previous studies had suggested a highly asymmetric structure for cdb3 and that pH dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 54 publications
5
69
0
Order By: Relevance
“…10 do not indicate any direct interactions between the peripheral domain of cdb3 and ankyrin repeats 22 and 23, although previous studies have shown that these repeats are important for high affinity binding (6,44). In previous work, it has been shown that the N-terminal domain of cdb3, which is composed of residues 1-54, is dynamically disordered in solution with no observable interactions between this domain and the central folded domain of cdb3 (17). However, when spin label side chains are placed at sequential positions along the central portion of the N-terminal domain, a restricted motion signal is observed when cdb3 is bound to AnkD34 (data not shown).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…10 do not indicate any direct interactions between the peripheral domain of cdb3 and ankyrin repeats 22 and 23, although previous studies have shown that these repeats are important for high affinity binding (6,44). In previous work, it has been shown that the N-terminal domain of cdb3, which is composed of residues 1-54, is dynamically disordered in solution with no observable interactions between this domain and the central folded domain of cdb3 (17). However, when spin label side chains are placed at sequential positions along the central portion of the N-terminal domain, a restricted motion signal is observed when cdb3 is bound to AnkD34 (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…Protein Preparation and Spin Labeling-The preparation and spin labeling of wild-type and single or double Cys mutants of cdb3 have been described in previous work (17). The cDNA encoding ankyrin repeats 13-24 plus 12 residues from the spectrin binding domain (AnkD34; residues 403-827) of ankyrin-R were provided by Dr. Peter Michaely (University of Texas, Southwestern).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the past decade, distance distribution measurements for pairs of spin labels with pulsed dipolar spectroscopy methods have been performed for a number of proteins with known structures [60,100,[128][129][130][131][132][133][134][135][136][137][138][139][140]. From these studies, a few were selected where mean distances were given and where the duration of the dipolar evolution was sufficient [21] for these mean distances to be reliable.…”
Section: Effects On Measurements Of Distance Distributionsmentioning
confidence: 99%
“…As a flexible arm would in essence be an unstructured, disordered segment, we chose an experimental approach that would provide specific measurements for any residue of interest, whether in a structured or unstructured region and that could be applied to intact chemoreceptors in their native or reconstituted membrane environment. Thus, we chose site-directed spin labeling and electron paramagnetic resonance (EPR) spectroscopy, a combination that has already provided useful information about disordered protein regions, [27][28][29][30][31][32] and Freeman, reproduced by permission). The ratio of the low-field to central peak amplitudes (top spectrum) can be used to derive a semiquantitative mobility parameter h(þ1)/h(0).…”
Section: Introductionmentioning
confidence: 99%